2010
DOI: 10.1111/j.1464-5491.2010.03144.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance, but not impaired fasting glucose, is a risk factor for early‐stage atherosclerosis

Abstract: Groups with impaired glucose tolerance and combined glucose intolerance had significantly higher brachio-ankle pulse wave velocity values compared with the group with normal glucose tolerance. Although the group with impaired fasting glucose showed a marginal increase in pulse wave velocity values compared with the group with normal glucose tolerance, the difference was not significant. Thus impaired glucose tolerance, but not impaired fasting glucose, is a risk factor for early-stage atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
3
24
1
Order By: Relevance
“…17) Previous studies suggest that increased fasting plasma glucose (FPG), which includes impaired glucose tolerance (IGT), impaired fasting glucose (IFG), and diabetes mellitus (DM), is a risk factor for arterial stiffness. [18][19][20] Homocysteine (Hcy), a sulphur-containing amino acid produced by the catabolism of dietary methionine, is a known risk factor for the cardiovascular system. 21) Zhou 22) and Gu 23) proved that Hcy levels in type II diabetes patients were associated with the development and progression of macrovasculopathy and eyeground vascular disease, and the mechanism may be related to insulin deficiency and (or) resistance which can influence blood pressure, lipid metabolism, and also affect the metabolism of Hcy.…”
mentioning
confidence: 99%
“…17) Previous studies suggest that increased fasting plasma glucose (FPG), which includes impaired glucose tolerance (IGT), impaired fasting glucose (IFG), and diabetes mellitus (DM), is a risk factor for arterial stiffness. [18][19][20] Homocysteine (Hcy), a sulphur-containing amino acid produced by the catabolism of dietary methionine, is a known risk factor for the cardiovascular system. 21) Zhou 22) and Gu 23) proved that Hcy levels in type II diabetes patients were associated with the development and progression of macrovasculopathy and eyeground vascular disease, and the mechanism may be related to insulin deficiency and (or) resistance which can influence blood pressure, lipid metabolism, and also affect the metabolism of Hcy.…”
mentioning
confidence: 99%
“…However, in addition to identifying a novel relationship between postchallenge hyperglycemia and cAIx and PPA, another novel aspect of our study is that we could demonstrate this in relatively young individuals (mean age 38), whereas the above studies examined individuals older than 50 years. As another limitation, but similar to the aforementioned studies on glycemia and PWV [17,18], we have measured all our parameters only once in each individual, and perhaps even closer correlations would have been found with repeat measurements and averaging of those measurements. Finally, there is evidence from prospective studies that 2-h glucose levels predict mortality better than impaired fasting glucose [5].…”
Section: Discussionmentioning
confidence: 87%
“…In addition to these crosssectional data, the progression of IMT over time is predicted closely by postchallenge glucose levels [16]. Furthermore, other studies demonstrated that the 2-h value of the OGTT is the most powerful metabolic predictor of arterial stiffness as determined by pulse wave velocity (PWV) measurements [17,18].…”
Section: Discussionmentioning
confidence: 98%
“…Plasma was separated from whole blood within 1 h after collection, and plasma glucose and HbA1c concentrations were determined as previously reported [7,8]. Brachial-ankle pulse wave velocity (baPWV) was also measured as previously reported 7,8 in order to compare our results and previous results from the point of research objectivity and suitability.…”
Section: Methodsmentioning
confidence: 99%